Agent-based Simulation of Fuel Distribution in Indonesia - Putro, Utomo Sarjono (SBM ITB, 2006)
Indonesia historically has maintained very large consumption subsidies for domestic retail fuel consumers. The Government announced that current subsidiary levels could not longer to be sustained, so it will be reduced. Since fuel is usually, smuggled overseas not the other way around, it cause a serious case such as illegal fuel. The poor people only enjoy 20% distribution fuel subsidy rather than rich people. Beside that, an opportunist actor does a serious case for public demand to get a large profit. Poorly, there is no clearly sanction for them. Meanwhile, it needs law enforcement to give sanction for opportunist actor. Interaction in this fuel distribution for law enforcement is very complex. In this research, we use fuel distribution model for petroleum, gasoline, and diesel fuel to secure fuel distribution using agent based simulation.Â Keywords:Â law enforcement, fuel distribution, agend-based simulation